Seeking Freedom through Variety - Levav, Jonathan; Zhu, Rui (Journal of Consumer Research, 2009)
This article examines the effect of spatial confinement on consumer choices. Building on reactance theory and the environmental psychology literature, we propose that spatially confined consumers react against an incursion to their personal space by making more varied and unique choices. We present four laboratory experiments and one field study to support our theorizing. Study 1 demonstrates that people in narrower aisles seek more variety than people in wider aisles. Study 2 indicates that this effect of confinement in narrow aisles also extends to more unique choices. Study 3 shows that perceptions of confinement exert their strongest influence on people who are chronically high in reactance. Study 4 suggests that influencing perceptions of confinement is sufficient to evoke variety seeking. Finally, the field study uses crowding as a proxy for confinement and finds a positive relationship between crowding and variety seeking in real grocery purchases.